Severe Acute Chest Syndrome in a Sickle Cell Patient That Required Repeated Exchange Transfusion - Saleh, Mohammed (Cureus, 2021)
Acute chest syndrome (ACS) is one of the major causes of mortality and morbidity in patients with sickle cell disease (SCD). ACS usually presents in a more severe form in adults older than 20 years. High clinical suspicion should be maintained in SCD patients who presents with painful crises. This case report presents an interesting severe form of ACS that, quite unusually, required repeated exchanged blood transfusion to achieve clinical improvement.